2020
DOI: 10.12659/msm.929527
|View full text |Cite
|
Sign up to set email alerts
|

Combining Blood-Based Biomarkers to Predict Mortality of Sepsis at Arrival at the Emergency Department

Abstract: Background Our aim was to determine a useful combination of blood biomarkers that can predict 28-day mortality of sepsis upon arrival at the Emergency Department (ED). Material/Methods Based on Sepsis-3.0, 90 sepsis patients were enrolled and divided into survivor and nonsurvivor groups with day 28 as the study end point. After comparing the demographic data and clinical characteristics of patients, we evaluated the predictive validity of a combination of markers includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Another study by Xie et al showed no association between NLR and 28-day mortality in patients diagnosed with sepsis (42). In a study done by Sari et al, the AUC of NLR at the rst day of ICU admission in septic shock patients was: 0.515 with a p-value of 0.73 (43).…”
Section: Discussionmentioning
confidence: 93%
“…Another study by Xie et al showed no association between NLR and 28-day mortality in patients diagnosed with sepsis (42). In a study done by Sari et al, the AUC of NLR at the rst day of ICU admission in septic shock patients was: 0.515 with a p-value of 0.73 (43).…”
Section: Discussionmentioning
confidence: 93%
“…Also, most of them provided data on the association between nonsepsis, sepsis, severe sepsis and septic shock and different blood lactate values. Meanwhile, there were 82 studies that demonstrated the relationship between blood lactate and sepsis induced mortality [9,11,15,19,31,34,36,[38][39][40][42][43][44][45][46][47][48][49][50][51]53,55,58,59,62,63,65,[67][68][69][70][71][72][74][75][76]78,81,83,85,[87][88][89]91,93,95,. Additionally, there were 46 articles reported the diagnostic accuracy of blood lactate levels in determining sepsis and associated clinical prognosis [11,15,31,33,34,38,43-45,50,53,56,59,64-67,69...…”
Section: Resultsmentioning
confidence: 99%
“…Sixty studies including 15,681 critically ill septic patients evaluated the role of at least one of our selected biomarkers for mortality prediction [ 23 62 ]. We contacted 11 study teams for additional information, and we received replies from three [ 27 , 33 , 56 ]. Fifty-five (91.7%) studies were published in the last 10 years (2012–2023), and 30 (50.0%) were published in the previous 3 years.…”
Section: Resultsmentioning
confidence: 99%